Mesh Migration into the J-Pouch in a Patient with Post-Ulcerative Colitis Colectomy: A Case Report and Literature Review. (23rd November 2017) - Ghanim, Asem; Smood, Benjamin; Martinez, Joseph; Morris, Melanie S.; Porterfield, John R.
Abstract : Mesh repair offers advantages like lower postsurgical pain and earlier return to work. Thus, it has become a widely used treatment option. Here, we present the first case report of a mesh migration into a J-pouch in a patient with history of ulcerative colitis who underwent total abdominal colectomy with J-pouch and ileoanal anastomosis and a subsequent laparoscopic ventral hernia repair with mesh.